Disruption of sex‐specific doublesex exons results in male‐ and female‐specific defects in the black cutworm, Agrotis ipsilon. Issue 6 (7th January 2019) - Chen, Xien; Cao, Yanghui; Zhan, Shuai; Tan, Anjiang; Palli, Subba Reddy; Huang, Yongping
Abstract: BACKGROUND: Doublesex ( dsx ), the downstream gene in the insect sex‐determination pathway, is a key regulator of sexually dimorphic development and behavior across a variety of insects. Manipulating expression of dsx could be useful in the genetic control of insects. However, information on the sex‐specific function of dsx in non‐model insects is lacking. RESULTS: In this work, we isolated a dsx homolog, which is alternatively spliced into six female‐specific and one male‐specific isoforms, from an important agricultural pest, the black cutworm, Agrotis ipsilon . Studies on the expression of sex‐specific Aidsx mRNA during embryonic development showed that the sixth hour post oviposition is the key stage for sex determination in A. ipsilon . Functional analysis of Aidsx was conducted using a CRISPR/Cas9 system targeting female‐ and male‐specific Aidsx exons. Disruptions of sex‐specific Aidsx exons resulted in sex‐specific, sexually dimorphic defects in external genitals, gonads and antennae, and expression of sex‐specific genes as well as production of offspring in both sexes. CONCLUSION: Our results not only demonstrate that dsx is a key player determining A. ipsilon sexually dimorphic traits, but also provide a potential method for the genetic control of this pest. © 2018 Society of Chemical Industry Abstract : CRISPR/Cas9‐mediated knockout of sex‐specific doublesex exons resulted in sex‐specific abnormal external genitals, which caused mutants to fail to mate and produce offspring.